2013
DOI: 10.1051/0004-6361/201321518
|View full text |Cite
|
Sign up to set email alerts
|

The effects of variations in nuclear interactions on nucleosynthesis in thermonuclear supernovae

Abstract: Context. Type Ia supernova explosions are violent stellar events important for their contribution to the cosmic abundance of iron peak elements and for their role as cosmological distance indicators. Aims. The impact of nuclear physics uncertainties on nucleosynthesis in thermonuclear supernovae has not been fully explored using comprehensive and systematic studies with multiple models. To better constrain predictions of yields from these phenomena, we investigate thermonuclear reaction rates and weak interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 78 publications
(102 reference statements)
1
72
3
1
Order By: Relevance
“…This is derived from the 53 Cr abundance given by ref. 24, but we note that different models produce very similar 53 Mn/ 55 Mn ratios (42 Mn ratio in SNIa would result from a 10-fold increase of the 32 S(β + ) 32 P decay (43), in which case T isolation would decrease to ' 9 My. This possibility needs to be further investigated.…”
Section: Snia Sourcementioning
confidence: 78%
“…This is derived from the 53 Cr abundance given by ref. 24, but we note that different models produce very similar 53 Mn/ 55 Mn ratios (42 Mn ratio in SNIa would result from a 10-fold increase of the 32 S(β + ) 32 P decay (43), in which case T isolation would decrease to ' 9 My. This possibility needs to be further investigated.…”
Section: Snia Sourcementioning
confidence: 78%
“…At lower density, the 55 Co present in NSE is readily destroyed during the alpha-rich freeze-out via 55 Co(p, γ) 56 Ni (see Jordan et al 2003), resulting in a much lower final [Mn/Fe]. We note that a recent study has shown that the 55 Co to 56 Ni production ratio is rather insensitive to nuclear reaction rate uncertainties (Parikh et al 2013). …”
Section: Nucleosynthesis Of Mn In Sn Iamentioning
confidence: 80%
“…Model yields where the primary WD is significantly less massive than M Ch predict even lower 57 Ni/ 56 Ni ratios: the merger model of a 1.1M e CO WD with a 0.9M e CO WD of Pakmor et al (2012) predicts ∼1.1 times Solar and the pure detonation models of CO and ONe WDs of Marquardt et al (2015) predict around 0.3-0.5 times Solar. Parikh et al (2013) have found that the 57 Ni/ 56 Ni production ratio is very robust (at the 10% level) to individual changes of nuclear reaction rates by a factor of 10; rate uncertainties are therefore unlikely to solely account for the difference. Therefore, the high 57 Co/ 56 Co ratio we find appears to point toward a near-M Ch progenitor.…”
Section: Expected 57 Co Yields From Sn Ia Explosion Modelsmentioning
confidence: 99%